Amphiphilic peptide-based MMP3 inhibitors for intra-articular treatment of knee OA. (15th May 2021) - Guarise, Cristian; Ceradini, Davide; Tessari, Martina; Pavan, Mauro; Moro, Stefano; Salmaso, Veronica; Barbera, Carlo; Beninatto, Riccardo; Galesso, Devis
Graphical abstract: Abstract: Since 2007, Metalloproteases (MMPs) have been considered potential targets for treating osteoarthritis (OA), for which the primary pathogenic event is the extensive degeneration of articular cartilage. MMP3 is an enzyme critical for these degenerative changes. However, problems of selectivity, low bioavailability and poor metabolic profile during clinical trials of MMPs inhibitors (MMPIs) led to limited beneficial effect and thus did not justify further pursuit of the clinical studies. In a previous work, a new alkyl derivative of hyaluronic acid (HA), HYADD4®, previously approved as intra-articular treatment for knee OA, was studied in vitro and in vivo as MMP3I. Molecular simulation studies confirmed the interaction between the alkyl side chain of this HA derivative and the additional S1′ pocket of MMP3. However, the high MW and the polar HA backbone of HYADD4® imply a high desolvation energy cost, which can potentially decrease its inhibitory potency. In this study, a new class of MMP3Is based on a small peptide backbone (CGV) chemically derivatized with an alkyl chain was developed through interactive cycles of design, synthesis and screening, accompanied by computational evaluation and optimization. Two MMP3Is, e(I) and l(II), were selected because of their effective inhibitory activity (3.2 and 10.2 µM, respectively) and water solubility. Both MMPIs showed a broad range of inhibitory effects against almost all the MMPs tested. In an in vitro model of inflammatory OA, e(I) was the most effective MMPI: at the concentration of 93 µM, it reversed inflammatory outcomes. Moreover, because of its amphiphilic structure, the e(I) MMPI promoted stable micellar formulation at concentrations higher than 0.2 mg/mL in water. The findings were confirmed by TEM and Nile red staining analysis. Based on these results, the e(I) MMPI can be considered a good candidate for the intra-articular treatment of OA, and the micellar formulation of this peptide in an aqueous buffer can potentially increase the bioavailability and, thus, the efficacy of the MMPIs.